Bottom-up silicon nanowire-based thermoelectric microgenerators. (November 2015) - Dávila, D; Huber, R; Hierold, C
Abstract: In this work, bottom-up intrinsic crystalline Si nanowire arrays in combination with top-down microfabrication techniques and a vertical device architecture have been proposed to develop an all-silicon nanostructured thermoelectric generator. To fabricate this device, a suitable vertical integration of Si NWs on patterned microstructures, which define the thermoelectric legs of the generator, has been achieved by bonding top and bottom silicon structures through nanowires. The process has been proven to be a feasible approach that employs a regrowth process of the nanowires for bonding purposes.